A Strong Convergence Theorem by the Shrinking Projection Method for the Split Common Null Point Problem in Banach Spaces. (2nd February 2016) - Hojo, Mayumi; Takahashi, Wataru
ABSTRACT: In this article, we consider the split common null point problem in Banach spaces. Then, using the shrinking projection method, we prove a strong convergence theorem for finding a solution of the split common null point problem in Banach spaces. It appears that such a theorem is a first in Banach spaces.